2009
DOI: 10.1093/jnci/djp023
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer and Chronic Obstructive Pulmonary Disease: Needs and Opportunities for Integrated Research

Abstract: Lung cancer and chronic obstructive pulmonary disease (COPD) are leading causes of morbidity and mortality in the United States and worldwide. They share a common environmental risk factor in cigarette smoke exposure and a genetic predisposition represented by the incidence of these diseases in only a fraction of smokers. The presence of COPD increases the risk of lung cancer up to 4.5-fold. To investigate commonalities in disease mechanisms and perspectives for disease chemoprevention, the National Heart, Lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
142
0
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(149 citation statements)
references
References 70 publications
1
142
0
6
Order By: Relevance
“…Lung cancers that arise from the lung parenchyma with abnormal and excessive inflammatory responses in COPD are thought to have an aggressive character. 26) Also, COPD often coexists with diseases such as cachexia, cardiovascular disease, osteoporosis and diabetes, which are all associated with systemic inflammation, 27) and such comorbidities might directly or indirectly affect prognosis. Determination of the basis of the association of GOLD 2/3 COPD with a worse prognosis may lead to better treatment and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancers that arise from the lung parenchyma with abnormal and excessive inflammatory responses in COPD are thought to have an aggressive character. 26) Also, COPD often coexists with diseases such as cachexia, cardiovascular disease, osteoporosis and diabetes, which are all associated with systemic inflammation, 27) and such comorbidities might directly or indirectly affect prognosis. Determination of the basis of the association of GOLD 2/3 COPD with a worse prognosis may lead to better treatment and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Boelens et al (2011) reported that a relationship exists between squamous cell lung cancer and COPD. Punturieri et al (2009) reported that the presence of COPD increases the risk of lung cancer by up to 4.5-fold. However, the mechanisms by which Cpn chronic infection induces lung cancer remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…По данным литературы, в 50-90% случаев рак легкого сочетается с хронической обструктивной болезнью легких, которая, как правило, ассоциирована с инфекцией в дыха-тельных путях, и протекает особенно тяжело [23,25,26]. Противоопухолевое лечение этой категории больных про-ходит с более частым развитием инфекционных осложне-ний в нижних дыхательных путях [12,15,23,25,26].…”
Section: диссертантunclassified
“…Противоопухолевое лечение этой категории больных про-ходит с более частым развитием инфекционных осложне-ний в нижних дыхательных путях [12,15,23,25,26].…”
Section: диссертантunclassified